The in-between bookstore eaudiobook A novel. - Underhill, Edward (HarperAudio, 2025)
"What would you tell your teen self if you could go back in time? Underhill's tender, innovative debut is the smartest take on this trope I've ever read. . . and for the record, I read it in a single sitting. A beautiful, thoughtful study of how we find our truest selves, and whom we choose to trust with that gift." — Jodi Picoult, #1 New York Times bestselling author A poignant and enchanting novel about a magical bookstore that transports a trans man through time and brings him face-to-face with his teenage self, offering him the chance of a lifetime to examine his life and identity to find a new beginning. When Darby finds himself unemployed and in need of a fresh start, he moves back to the small Illinois town he left behind. But Oak Falls has changed almost as much as he has since he left. One thing is familiar: In Between Books, Darby's refuge growing up and eventual high school job. When he walks into the bookstore now, Darby feels an eerie sense of déjà vu—everything is exactly the same. Even the newspapers are dated 2009. And behind the register is a teen who looks a lot like Darby did at sixteen. . . who just might give Darby the opportunity to change his own present for the better—if he can figure out how before his connection to the past vanishes forever. The In-Between Bookstore is a stunning novel of love, self-discovery, and the choices that come with both, for anyone who has ever wondered what their life might be like if they had the chance to go back and take a bigger, braver risk.